ANALISIS TINGKAT LITERASI KEUANGAN SYARIAH MAHASISWA PASCASARJANA UINFAS BENGKULU: PERBANDINGAN ANTARA BANK SYARIAH DAN BANK KONVENSIONAL - Ahmad Rayendra; Fatimah Yunus; Gustiya Sunarti (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study aims to analyze the level of Islamic financial literacy among students at UIN Fatmawati Sukarno (UINFAS) Bengkulu and compare their understanding of the products and services offered by Islamic banks and conventional banks. Islamic financial literacy is an individual's ability to understand Islamic financial principles, including the prohibitions on usury, gharar, and maisir, as well as the use of instruments such as mudharabah, musyarakah, and murabahah. The research method used is descriptive quantitative, with questionnaires distributed to 120 students who actively use banking services. The results show that the level of Islamic financial literacy among students is generally in the fairly good category, but there are differences in understanding between students who use Islamic banks and conventional banks. Students who use Islamic banks have a higher level of understanding of Islamic financial principles compared to students who use conventional banks. These findings demonstrate the importance of improving Islamic financial literacy education for students, including those who primarily use conventional banks, to raise awareness of Islamic financial principles in everyday life.